Effects of Interpersonal Sensorimotor Synchronization on Dyadic Creativity: Gender Matters - Gaggioli, Andrea; Falletta, Elisa Maria; Ferrise, Francesco; Graziosi, Serena; Gallace, Alberto; D’Ausilio, Alessandro; Cipresso, Pietro; Riva, Giuseppe; Chirico, Alice (Frontiers in Psychology, 2019)
Although it is noted that interpersonal sensorimotor coordination can influence several high-level socio-cognitive processes, its impact on creative collaboration is nearly unexplored. Here, we investigated the effects of a form of sensorimotor coordination, that is, sensorimotor synchronization, on a subsequent creative collaboration task. 60 pairs (n total. = 120 participants) formed by previously unacquainted individuals performed a tower-building task either jointly or alone, followed by a dyadic creativity task. Tower building time in the joint condition was recorded through a sensorized platform and creativity performance was evaluated by two independent raters based on the quantity and quality of generated ideas. We controlled for gender composition and for the disposition to cooperate and to adopt a creative, analytical style. Results showed that male-male couples were more creative after the joint-action condition, whereas female-female and mixed-gender couples were more creative after the solo condition. Regression analyses of tower building time on creativity performance revealed that building time was a significant predictor of creativity dimensions in male-male and in mixed-gender couples but did not predict creative performance in female-female couples. Overall, these findings suggest that the manipulation of sensorimotor coordination can influence performance in a subsequent creative collaboration task, with the nature and magnitude of this effect depending on the gender composition of the dyads. These results have potential implications for the design of sensorimotor-based strategies to enhance dyadic creative performance in several contexts, especially for the organizational settings.